Pengembangan Aplikasi Stunting Care untuk Pemantauan Pertumbuhan Anak - Calvin Rinaldy Leonard; Ayu Arista; Muhammad Kurnia; Rahmawati; Muhammad Rachmat (Warta LPM, 2024)
Recording the results of conventional child growth measurements in the Maternal and Child Health book has long been carried out by health workers and posyandu cadres at the Bontoharu Community Health Center, Selayar Regency, and posyandu cadres in Bontotangnga Village. This form of recording takes quite a lot of time, is prone to errors, and the results do not display attractive visualizations, so a reliable form of recording is needed to monitor children's growth as an effort to prevent and treat stunting. The method used in this community service is Community Based Research (CBR). To overcome the problem of stunting early, the Stunting Care application was developed. Stunting Care is an application for monitoring children's growth periodically by entering data on the child's height and weight. This application will provide predicted results for children, whether they are stunting, at risk of stunting, normal or high normal and is equipped with various features. The Stunting Care application was developed using agile development software engineering methods and through black box testing. The test results of the Stunting Care application are classified as good, as indicated by the system functionality running smoothly.